Manufacturing Competitiveness in Asia - Jomo, K. S. (Routledge Studies in the Growth Economies of Asia, 2003)
There are competing theories to explain the reasons behind the international competitiveness of manufacturing in Asia. Analysing these different theories will bring important lessons, not just for Asia, but for developing economies the world over. This lucid book studies industries and firms in East Asia and examines the major determinants of their economic performance. With contributions from such leading thinkers as Ha-Joon Chang and Rajah Rasiah, the book covers such themes as: *industrial policy and East Asia *Taiwan's information technology industry *The role of the government in technological capability building Manufacturing Competitiveness in Asia touches on many important themes and issues and as such will be of great interest to students, academics and policy-makers involved in industrial economics, international trade and Asian studies.